Environmental information systems : the development and implementation of the Lake Rukwa Basin integrated project environmental information system (LRBIP-EIS) database, Tanzania - Paradzavi, Charles (School of Architecture, Planning and Geomatics, 2015)
Bibliography: leaves 91-97.